Disorder, critical currents, and vortex pinning energies in isovalently substituted BaFe2(As1_xPx)2 - Demirdis, Sultan (2013)
We present a comprehensive overview of vortex pinning in single crystals of the isovalently substituted iron-based superconductor BaFe2(As1−xPx)2, a material that qualifies as an archetypical clean superconductor, containing only sparse strong pointlike pins [in the sense of C. J. van der Beek et al., Phys. Rev. B 66, 024523 (2002)]. Widely varying critical current values for nominally similar compositions show that flux pinning is of extrinsic origin. Vortex configurations, imaged using the Bitter decoration method, show less density fluctuations than those previously observed in charge-doped Ba(Fe1−xCox)2As2 single crystals. Analysis reveals that the pinning force and energy distributions depend on the P content x. However, they are always much narrower than in Ba(Fe1−xCox)2As2, a result that is attributed to the weaker temperature dependence of the superfluid density on approaching Tc in BaFe2(As1−xPx)2. Critical current density measurements and pinning force distributions independently yield a mean distance between effective pinning centers L∼90 nm, increasing with increasing P content x. This evolution can be understood as being the consequence of the P dependence of the London penetration depth. Further salient features are a wide vortex free “Meissner belt”, observed at the edge of overdoped crystals, and characteristic chainlike vortex arrangements, observed at all levels of P substitution.